Preloading Trifolded Grafts for Descemet Membrane Endothelial Keratoplasty Affects Scroll Formation. Issue 8 (August 2020) - Solar, Steven J.; Deljookorani, Shiva; Wiener, Batya G.; Rosen, Allison; Chaurasia, Akash; Shahmirzadi, Monady; Meshkin, Ryan S.; Dzhaber, Daliya; Chiang, Eric; Barnes, Kali; Chen, Conan Y.; Koo, Ellen H.; et al.
Abstract : Purpose: The trifolded, endothelium-in approach to Descemet membrane endothelial keratoplasty (DMEK) facilitates tissue insertion into the anterior chamber. We hypothesized that preloading the trifolded donor grafts in a cartridge for 48 hours before insertion would induce biomechanical changes that decrease their scrolling tendency compared with those loaded immediately before insertion. Methods: Ten Descemet membrane donor grafts, peeled and cut to 8.0 mm, were prepared by a single eye bank technician. Each graft was trifolded and pulled into a DMEK cartridge and stored for 48 hours. They were then pulled with microforceps into a petri dish filled with balanced salt solution. A video was recorded of the graft becoming a scroll over a 2-minute period. Each graft, serving as its own control, was then trifolded, pulled into the cartridge, and the process repeated. Images from 1, 5, 10, 60, and 120 seconds were extracted from video recording of the procedures. Scroll width was analyzed by graders masked to group assignment. A paired t test was used to determine differences in scroll width at each time point between the 48-hour and instant trifolding conditions. Results: All grafts scrolled after removal from the cartridge into balanced salt solution. We measured a significant difference at all time points 1 through 120 seconds (4.02 preloaded vs. 2.91-mm instant trifold, P = 0.035). Conclusions: Preloading DMEK grafts in a trifolded configuration for 48 hours reduces the scrolling tendency of Descemet membrane for at least 2 minutes. Abstract : Supplemental Digital Content is Available in the Text.